Óleo de babaçu: uma plataforma para obtenção de biocombustíveis - Leonardo Gomes de Abreu (2023)
Drop-in fuels represent the class of biofuels that most closely resemble fossil fuels due to their chemical composition, with aviation bio-kerosene (BioQAV) being a notable example. Currently, there are seven certified routes, and the Hydroprocessing of Esters and Fatty Acids (HEFA) route is the most promising from an industrial perspective. The HEFA route uses vegetable oils and animal fats as raw materials to produce bio-hydrocarbons. In this study, babassu oil was chosen as the raw material due to its short hydrocarbon chain, eliminating sequential steps like hydrocracking to fit within the BioQAV range. Babassu oil was characterized using infrared spectroscopy and gas chromatography. Additionally, tests were conducted to determine acidity indices, relative density, and fatty acid profiles. Ruthenium monometallic, bimetallic, and bifunctional catalysts were prepared using the sol-gel method. The Ru/SiO2 and RuSn/SiO2 catalysts were characterized by X-ray diffraction, temperature-programmed reduction, N2 BET adsorption/desorption isotherm, and BJH pore size distribution. Batch reactions were carried out in a Parr 4348 reactor using babassu oil, four catalysts, a temperature range of 300 to 350 °C, H2 pressure ranging from 20 to 30 bar, reaction time varying from 1h15 to 3h30, and 150 rpm. The conversion of the liquid product in all reactions was above 85%. The most promising product was obtained with the Ru/SiO2 catalyst at 350 °C, 30 bar H2, 2h30 reaction time, with a liquid product conversion of 98% and BioQAV selectivity of 72%. The analyzed physicochemical properties are in accordance with ASTM D75566 standards, except for the freezing point. Coprocessing of babassu oil and α-pinene in a 1:1 ratio was conducted at 350 °C, 30 bar H2, for 2h30, resulting in a liquid product conversion of 99.5% to bio-hydrocarbons, with a BioQAV selectivity of 89%. Thus, this study demonstrated the technical feasibility of producing bio-kerosene from vegetable oil.